LOTS AND HOTS OF TEACHER-MADE TEST IN JUNIOR HIGH SCHOOL LEVEL IN KEFAMENANU - Maria Wihelmina Wisrance; Thresia Trivict Semiun (JEE (Journal of English Education), 2020)
This study was aimed at examining the quality of teacher-made English summative test of grade VII and VIII of one of Junior High Schools in Kefamenanu. It applied the descriptive qualitative method by focusing on document analysis. The result showed that both tests given to the first and second-grade students of Junior High School of Biboki Utara are applied on 2 levels of Bloom Taxonomy Revised Theory, they are Remembering (C1) and Understanding (C2). The result of the test indicated that the tests are included in the lowest level of the cognitive domain based on Bloom Taxonomy Revised theory. Besides, certain test instructions in both test A and B needed to be paid more attention since they contain some grammatical errors.